2016
DOI: 10.5614/j.eng.technol.sci.2016.48.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior towards Safer Car Purchasing Decisions

Abstract: Abstract. In Malaysia, the car safety level has been elevated through regulations and a consumer-based approach, i.e. the New Car Assessment Program in Southeast Asian Countries (ASEAN NCAP). Nevertheless, the availability of information on consumers' car purchasing decisions towards safety is still limited in Malaysia. Thus, this study was aimed at evaluating consumers' purchasing decisions of their present cars and investigating their awareness of ASEAN NCAP. Self-administered questionnaires were distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The finding suggests that car corporations need to focus on these three variables to increase their sales of new vehicles. Kassim et al (2016) and Hung and Yazdanifard (2015) suggest that safety is considered to be one of the top three factors when purchasing a car among consumers in Malaysia. This information is essential for policy makers, manufacturers, and other stakeholders to assist in setting priorities regarding the promotion of car safety in the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The finding suggests that car corporations need to focus on these three variables to increase their sales of new vehicles. Kassim et al (2016) and Hung and Yazdanifard (2015) suggest that safety is considered to be one of the top three factors when purchasing a car among consumers in Malaysia. This information is essential for policy makers, manufacturers, and other stakeholders to assist in setting priorities regarding the promotion of car safety in the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Application area Used methods Park et al (2006) Airline service quality and passengers' future behaviour retention Hybrid MCDM Wang and Tzeng (2012) Band marketing for creating brand value DEMATEL, ANP, VIKOR Haverila (2011) To select the feature of mobile and repurchase retention Hybrid Nilashi and Ibrahim (2014) Purchasing intentions business to consumer Hybrid Liu et al (2013) How improving services in metro-airports can help tourism development Hybrid Chiu et al (2013) Prediction of consumers' repurchase intention for improving e-store business DEMATEL, ANP, VIKOR de Dienes Alicia (2011) Functional food products and consumer repurchase retention AHP and Choice Based Conjoint Huang et al (2012) Identifying influencing factors for smart phone operation systems DEMATEL and SEM Hu et al (2014) Exploring smart phone improvements and customers' repurchase retention Hybrid Khatwani et al (2014) Evaluating internet information search channels Hybrid Anand et al (2015) Comparative analysis about intention among gender Hybrid Khatwani and Das (2016) Understanding information given by internet channels Hybrid Maymand et al (2017) Factors effecting shopping behaviour of foreign tourists Hybrid Lin et al (2016) E-service quality performance and e-store VIKOR Chiang (2016) Fair trade products purchase AHP Yogi (2015) Measuring the customers' intention about quality Fuzzy Logic Rekik et al (2016) Assessing e-commerce web sites ranking Fuzzy ANP Kumar and Dash (2017a) Measuring and evaluating e-malls on their technical and web dimensions Fuzzy Delphi, Fuzzy TOPSIS Kumar et al (2017a) Comprehensive evaluation of internet shopping malls AHP, TOPSIS Kumar and Dash (2017b) Measuring repurchase intention of online consumers Fuzzy Delphi and DEMATEL Kumar and Dash (2016c) Consumer decision-making in e-marketplace DEMATEL Tajadod et al (2016) Maintenance strategy selection and retention Hybrid Bouguerra et al (2012) How customers accept different maintenance policies Hybrid Cui et al (2017) Selecting a remanufacturing quality strategy based on consumer preferences Hybrid Kassim et al (2016) Consumer behaviour towards safer car purchasing decisions Hybrid Padilla et al (2017) Service value on r...…”
Section: Authorsmentioning
confidence: 99%
“…Preventive maintenance helps in reducing failure during the normal life of equipment (Mashhadi et al, 2016). Service providers aim to give their best and are keen to monitor customer expectations (Kassim et al, 2016;Padilla et al, 2017;Chiu et al, 2016;Li et al, 2017). But after conducting a sample survey with automobile company employees, our research team learned that this particular company retained 84% consumers during the first year of the Free Service Coupon (FSC) period, dropping to 29% in the second year.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3, consumers can create pressure onto OEMs by supporting the safety rating. A continuous assessment by MIROS showed that consumer awareness about ASEAN NCAP initiative is on the rise (Table 2) (Abu Kassim et al, 2016b;Md Isa et al, 2014, 2016Mohd Jawi et al, 2014). In addition, ASEAN NCAP YouTube channel is able to gain more than two million views and is subscribed by more than seven thousand users, with the majority of them from Malaysia (37%), Indonesia (30%) and India (10%).…”
Section: Cop Rating Vs Score Percentagementioning
confidence: 99%